Blended Learning Based on Experiential Learning for Self-Regulated Learning Mathematics Education Students - Yani Supriani; Rina Oktaviyanthi; Ria Noviana Agus (Budapest International Research and Critics University, 2022)
Scientific skill is a special skill helping students to develop their knowledge. Indirectly, well-developed scientific skills will lead them to actively get involved. This special skill needs to be developed through cognitive skills. One of the developed affective skills is self regulated learning. Such skill is developed through blended learning basic experiential learning. This research involves 26 students in mathematics education, University of Serang Raya. This research focuses on topics about line, angle, triangle, and rectangle. This research is quasi experimental research with One Group Pretest Posttest Design using Purposive Sampling technique. The result of analysis shows that students' mathematical justification skill of Junior High School gives positive contribution through experiential learning.